Core-shell structured graphene aerogels with multifunctional mechanical, thermal and electromechanical properties. (June 2020) - Afroze, Jannatul Dil; Abden, Md Jaynul; Yuan, Ziwen; Wang, Chaojun; Wei, Li; Chen, Yuan; Tong, Liyong
Abstract: Many engineering applications demand lightweight materials with multifunctional mechanical properties. Graphene aerogels (GAs) have emerged as a potential candidate. However, GAs reported so far exhibit weak mechanical strength. Here, we report a two-step freezing method with assistance of borate cross-linkers to synthesize a core-shell structured GA. The large temperature gradient can control the nucleation and growth of ice crystals, leading to the formation of a densely packed core and sparsely packed shell. This unique structure can be turned for high compressive strength (43.43 kPa at 50% strain) and elasticity through consecutive distribution of mechanical loads between the core and shell. It can fully recover from 70% strain and 100 compression cycles under 50% strain. The GA also shows excellent compression sensitivity to electrical resistance, and the first-ever reported creep resistance for GAs with negligible residual strain under a static force of 4 kPa up to 200 °C in the air. The as-formed core-shell GAs exhibit stable piezoelectric effects, ultralow thermal conductivity (∼0.023 W m −1 K −1 ) and superior electrical conductivities (up to 52.99 S/m at 70% strain). The unique architecture and its multifunctional mechanical properties make it promising for a range of applications, including flexible sensors, actuators, thermal insulation, and electronics. Graphical abstract: Image 1